Dynamique d'apprenance dans une recherche collaborative portant sur la didactique de l’oral en contexte plurilingue : regards croisés - Véronique Miguel-Addisu; Sophie Beaumont (Recherches en didactique des langues et des cultures)
In the field of collaborative research in the didactic of languages, the actors of research-training projects postulate that collaboration meets the needs of both practitioners and researchers. Yet as it happens, the expected results do not reveal the same epistemology (practical and/or academic). However, if collaboration is possible, our premise is that it is thanks to the existence of triggers, which do not only include people skills, fortuitous encounters, or even shared ethics specific to collaborative researches. The basic principle is that collaboration is possible and even wanted as a benefit for each participant, pupils included. We will discuss from a collaborative research-training project in the area of the didactic of languages. The project ‘Schools, Pupils’ Languages and Plurilingualism: a collaborative research in the International French School of San Francisco – AEFE, USA (E2PRC_Francisco)’ is dealing with the didactic of oral language in a plurilingual context and gathers 9 teachers, 2 trainers for teachers, 4 researchers, 1 French inspector of education. We will more specifically focus on how researchers and trainers collaborate, through the double point of view of the co-pilots of the project who shared the writing. The article starts with a description of the context, and we will then demonstrate how the sociolinguistic data helped to achieve a shared approach of self-directed learning. We will finally detail the transformations and professional consequences initiated by such a conceptual framework for the trainers as well as for the co-pilots.